2022
DOI: 10.1016/j.asmr.2021.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Capsulolabral Adhesions After Hip Arthroscopy for the Treatment of Femoroacetabular Impingement: Strategies During Rehabilitation and Return to Sport to Reduce the Risk of Revision

Abstract: This article will review various strategies such as passive range of motion modalities, active range of motion movements, and pharmacological interventions for the prevention of adhesion formation after hip arthroscopy. Capsulolabral adhesions are a common cause of revision hip arthroscopy for which treatment methods are still evolving. Efforts to prevent and limit their formation postoperatively, including adjuncts such as losartan, as well as the use of consistent passive and active, multiplanar movements, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The authors reported good outcomes in the majority of patients, without any conversions to arthroplasty, lending support for our surgical approach. However, a less invasive technique for bone grafting is preferable in the setting of acetabular and/or femoral osteotomy to facilitate rehabilitation 18,21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported good outcomes in the majority of patients, without any conversions to arthroplasty, lending support for our surgical approach. However, a less invasive technique for bone grafting is preferable in the setting of acetabular and/or femoral osteotomy to facilitate rehabilitation 18,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Clohisy et al 12 used an anterior arthrotomy with simultaneous PAO and DFO in young adults with severe hip disease. However, anterior arthrotomy leads to prolonged surgical times when performed with PAO, complicates PAO recovery due to excessive adhesions, and is inferior to arthroscopy for intra-articular work 18,21,22 . Furthermore, Ko et al 23 detailed the utilization of a “trap door” bone grafting technique with a concomitant acetabular and/or femoral osteotomy to treat 9 adolescents with femoral head osteonecrosis and collapse of the articular surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, hip arthroscopy has been increasingly performed for the treatment of this intra-articular hip disorder along with cartilage and labral injuries [ 4 , 7 , 42 ]. As the annual number of procedures has increased, many studies have sought to evaluate the risk of undergoing a subsequent revision hip arthroscopy [ 1 , 2 , 5 , 6 , 9 , 11 , 12 , 14 , 17 , 23 , 28 , 32 , 34 , 38 ]. Though these studies have identified several risk factors associated with revision surgery, the ability to translate these pre-operative factors into a specific risk score is poor.…”
Section: Introductionmentioning
confidence: 99%